DOES PSYCHOLOGICAL OWNERSHIP AFFECT GREEN ORGANIZATIONAL BEHAVIOR? Received: 31st December 2021; Revised: 29th March 2022, 8th April 2022; Accepted: 13th April 2022 - Ozbozkurt, Onur Basar; Ince, Mehmet; Yesilkus, Fatma (PEOPLE: International Journal of Social Sciences, 2022)
This paper explores the impact of psychological ownership in an organizational plane on green organizational behavior, which plays a significant role in creating a sustainable environment and helps mitigate ecological issues of the world. The present study aims at being fulfilled the research gap by exploring the impact of psychological ownership on green organizational behavior. To this end, the data was collected from 237 employees working at one of the leading fastener manufacturers in Turkey by using the convenience sampling method. The data obtained from the questionnaire has been analyzed via “SPSS 26.0”. Our findings suggest that psychological ownership has a statistically significant impact on green organizational behavior and contributes to theoretical and practical implications.